Political and economic parameters of optimization of the fitness industry as a socio-natural system - Путятіна, Галина (Slobozhanskyi Herald of Science and Sport, 2019)
Galina Putiatina Purpose: justification of the research methodology of the politico-economic parameters of the optimization of the fitness industry as self-organized and socio-natural systems. Material & Methods: in the course of the study, the following methods were used: theoretical analysis and synthesis of data from scientific and methodological sources was used to determine the problematic field of functioning of the fitness industry and the state of its scientific and methodological processing. To create a theoretical basis for the concept of optimizing the industry of fitness, the methods of induction, deduction, analysis (structural-functional analysis), synthesis, synthesis, comparison, abstraction, analogy are applied. The expediency of using the method of mathematical modeling in the process of forecasting the development of the fitness industry has been substantiated. Results: use of the basic principles of the theory of functioning and development of self-organizing systems make it possible to determine the parameters of the fitness field as a socio-natural system with the aim of its optimization, effective management, forecasting. Conclusion: the necessary requirements for optimizing management in the field of fitness in a holistic state management system are the following parameters: continuous synchronization in each other’s relationship with the needs and the need to satisfy them; compliance with the required level of monitoring the development of the industry; sufficient controllability of the industry; ensuring sustainability and reliability of its operation. The actual lack of state regulation of the performance and development of the industry leads to inconsistency in the interaction of its elements as an integrated system. This process can lead to oversaturation of production and the growth of crisis, destruction and economic damage.